KAJIAN LITERATUR IMPLEMENTASI ETIKA DIGITAL DALAM PERSPEKTIF MANAJEMEN SUMBER DAYA MANUSIA PADA MAHASISWA PERGURUAN TINGGI - Nuryadi Nuryadi; Dewi Anjani; Sukma Ludda E.P; Genies Fitri O; Fassa Lukshod (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze and synthesize the concept of digital ethics from a Human Resource Management (HRM) perspect ive and its relationship with the development of student professional ism in higher education. The research employs a qualitative approa ch using a narrative literature review method of 18 scientific articles published between 2017 and 2025 and indexed in Google Scholar. The findings of the literature review indicate that digital ethics serves as a normative foundation in shaping students’ digital professional ism, particularly in managing digital identity and online reputation. The relationship between digital ethics and professionalism is not always direct, as it is influenced by mediating factors such as digital literacy, academic culture, institutional policies, and students’ level of commitment. From an HRM perspective, digital ethics should be positioned as part of behavioral competency integrated into character development and students’ work readiness. This study highlights the importance of integrating digital ethics into human resource development systems in higher education to foster adaptive and responsible professionals in the era of digital transformation.